2018
DOI: 10.1080/19401493.2018.1501095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two genetic algorithms minimizing carbon footprint of energy and materials in a residential building

Abstract: The emergence of building performance optimization is recognized as a way to achieve sustainable building designs. In this paper, the problem consists in minimizing simultaneously the emissions of greenhouse gases (GHG) related to building energy consumption and those related to building materials. This multi-objective optimization problem involves variables with different hierarchical levels, i.e. variables that can become obsolete depending on the value of the other variables. To solve it, NSGA-II is compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Fonseca et al [25] proposed a methodology to evaluate building energy and comfort performance while considering life cycle cost. Gagnon et al [26] developed an integrated system to compare an NSGA II optimization and a hierarchical optimization technique performance in minimizing the carbon footprint of building energy consumption and materials. The results of the study indicated that the NSGA II optimization methodology is better in identifying the optimal designs.…”
Section: Related Studiesmentioning
confidence: 99%
“…Fonseca et al [25] proposed a methodology to evaluate building energy and comfort performance while considering life cycle cost. Gagnon et al [26] developed an integrated system to compare an NSGA II optimization and a hierarchical optimization technique performance in minimizing the carbon footprint of building energy consumption and materials. The results of the study indicated that the NSGA II optimization methodology is better in identifying the optimal designs.…”
Section: Related Studiesmentioning
confidence: 99%
“…Likewise, the most common evolutionary search techniques have demonstrated their limitations in certain design problems within the field of architecture (Gagnon, Gosselin, Park, Stratbücker and Decker, 2019) (Wortmann, Waibel, Nannicini, Evins, Schroepfer and Carmeliet, 2017). Therefore, more sophisticated heuristic optimisation techniques are bound to become more viable alternatives in the future (LaTorre, Muelas and Peña, 2015).…”
Section: Bimbot Applied Artificial Intelligencementioning
confidence: 99%
“…Un aspecto importante a considerar es que los mecanismos de PCG que usan técnicas de búsqueda heurística (por ejemplo algoritmos evolutivos) tienden a requerir un número de evaluaciones de soluciones tentativos que puede ser medianamente alto, para ello se sugiere usar técnicas de surrogados que agilicen el proceso de evaluación descartando soluciones potencialmente poco interesantes antes de evaluarlas (Karavolos, Liapis and Yannakakis, 2009: 1). Asimismo, las técnicas de búsqueda evolutiva más habituales han demostrado sus limitaciones en determinados problemas de diseño dentro del campo de la arquitectura (Gagnon, Gosselin, Park, Stratbücker and Decker, 2019) (Wortmann, Waibel, Nannicini, Evins, Schroepfer and Carmeliet, 2017). Es por ello que técnicas más sofisticadas de optimización heurística están llamadas a ser alternativas más viables en el futuro (LaTorre, Muelas and Peña, 2015).…”
Section: Bimbot Inteligencia Artificial Aplicada Características Téunclassified
“…There have been different modifications applied in the GA to resolve the shortcomings in the GA. Examples of these modifications include, Micro-GA, which uses a smaller population size and uses reinitialization, 36 and different variations of the Non-dominated Sorting Genetic Algorithm (NSGA), including NSGA and NSGA-II, which applies non-dominated sorting strategy and niching, 37 structured NSGA (sNSGA), designed to deal with hierarchical variables, 38 and Elitist Non-dominated Sorting Evolution Strategy, a two-phase optimization using the GA (PR-GA), and the epsilon dominance multi-objective evolutionary algorithm. 39 While there have been improvements in specific aspects of the GA using the modifications, there still needs further investigation in this area.…”
Section: Overview and Backgroundmentioning
confidence: 99%
“…In a comparative study of GA and micro-GA by Gagne and Andersen, 17 the tendency of the micro-GA to trap in local optimum and the inconsistency in results of the GA are mentioned as shortcomings of the optimization methods whereas the latter can be overcome with multiple runs. In a comparative analysis of the NSGA-II and sNSGA by Gagnon et al., 38 dual mutation rate, decreasing during the process and allowing to mate high-level variables are introduced as the potential modifications to sNSGA to improve its performance.…”
Section: Overview and Backgroundmentioning
confidence: 99%